A Survey of Hong Kong's Putonghua Teaching in Primary and Secondary Schools from the Perspective of Cultural Identity - Suye Qi; Yanni Guo (Canadian Journal for New Scholars in Education)
Since the implementation of the "biliteracy and trilingualism" policy, Hong Kong's Putonghua teaching has seen certain advancements, yet it is not widely taught in primary and secondary schools. This may affect students' identification with Chinese culture. This paper investigates this issue across six aspects: family environment, interpersonal interaction, school education, social development, social values, and social culture. It finds a strong connection between Putonghua learning and cultural identity. Students taught Putonghua for longer periods are more likely to embrace Chinese culture and possess a stronger sense of national identity. The paper also proposes new ideas for Putonghua teaching in Hong Kong, focusing on avoiding reductive cultural identity, improving language learning integration, promoting productive cultural identity, and exploring the social value of Putonghua and enhancing the instrumental value of language learning.